The giant that makes do with little: small and easy-to-leave home ranges found in the giant root-rat - Šklíba, Jan; Vlasatá, Tereza; Lővy, Matěj; Hrouzková, Ema; Meheretu, Y; Sillero-Zubiri, C; Šumbera, Radim (Wiley-Blackwell, 2020)
Mammalian space-use patterns are largely determined by the resources utilized as well as by given habitat characteristics, as can be illustrated by rodents displaying predominantly subterranean activity. These rodents are largely limited in their use of space by their burrow systems. This results in smaller home ranges than is usual for rodents of a similar size. However, there is little information regarding how stable these home ranges are over time. We studied space use in the giant root-rat, Tachyoryctes macrocephalus, a large fossorial rodent endemic to the Bale Mountains of southern Ethiopia where it is the principal prey of the Ethiopian wolf Canis simensis. We radio-tracked 22 root-rats during a period of 36 days in the early dry season and 17 of them once again during a period of 37 days in the late dry season. The root-rats occupied very small (around 100 m(2)) home ranges which were often tightly packed, especially on a wetland shore that was a part of the study locality, but displayed little overlap. Almost 30% of the radio-collared root-rats of either sex dispersed (80-428 m from their original home range) during the 5 months of the study, mostly in a period between the early and late dry season characterized by a decreasing food supply and the soil becoming dry and hard. Individuals who did not disperse during this time usually shifted their home range. Root-rats living on the wetland shore, which were the largest and therefore likely competitively strongest individuals, shifted their home ranges into the wetland, likely for the purpose of increasing their food supply.
Keywords: dispersal; radio tracking; space use; home range; fossorial rodent; Tachyoryctes; Afroalpine; subterranean